2011
DOI: 10.1007/s11096-011-9539-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication practices among adult population attending community pharmacies in Malaysia: an exploratory study

Abstract: Self-medication practice is prevalent in Kuala Lumpur but some practice might be harmful. Education on appropriate use of self-medication need to be emphasized in order to ensure quality use of medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 9 publications
(18 reference statements)
7
45
4
2
Order By: Relevance
“…About 65% of respondents thought that over-the-counter medicines are as effective as those prescribed by the doctor. The finding was approximate to that reported by Hassali et al [14] in Malaysia (62.7%). As for personal behavior if experienced adverse reactions with medicines, 60.4% and 26.5% of the participants said that they consult treating doctor and pharmacist respectively, this is in accordance with a study conducted in Danish population which revealed that 73% and 35.2% consulting doctor and pharmacist respectively if experienced adverse reactions [15].…”
Section: Discussionsupporting
confidence: 88%
“…About 65% of respondents thought that over-the-counter medicines are as effective as those prescribed by the doctor. The finding was approximate to that reported by Hassali et al [14] in Malaysia (62.7%). As for personal behavior if experienced adverse reactions with medicines, 60.4% and 26.5% of the participants said that they consult treating doctor and pharmacist respectively, this is in accordance with a study conducted in Danish population which revealed that 73% and 35.2% consulting doctor and pharmacist respectively if experienced adverse reactions [15].…”
Section: Discussionsupporting
confidence: 88%
“…15 Almost 6% had experience the experienced adverse reactions such as gastrointestinal disturbance like constipation, diarrhoea, distension analogous to the result obtained from study done in Mangalore. 16 The current study showed that more than half of the respondents (54%) had good knowledge on over-thecounter drugs similar to a study from Nigeria i.e.…”
Section: Discussionsupporting
confidence: 63%
“…9,10 Better understanding of diseases and health, growth in information technology, number of available medications, and drug information have been identified as key factors contributing to increase in self-medication practices in the last decade. [11][12][13] Based on this, authors searched publications for the last 15 years i.e. between 1 st January 2000 and 31 st December 2015 from databases namely PubMed, and Web of Science.…”
Section: Methodsmentioning
confidence: 99%